Workshop menghindari plagiasi dengan teknik parafrase pada penulisan karya ilmiah mahasiswa tingkat akhir 2021 - Lina, Marisa Fran; Supriyono, Lilik (Penamas: Journal of Community Service, 2021)
Scientific paper often becomes the toughest obstacle faced by students. This community service article was written based on a workshop with the same theme which aims to avoid plagiarism on writing scientific papers for final-year students in Salatiga with paraphrasing techniques. The workshop was held online via Zoom application and joined by 20 eight-semester students in Salatiga 2021 who had difficulties in writing their final assignments. The activities were: material presentation on paraphrasing techniques, question and answer session, paraphrasing techniques practice directly from scientific text sources according to the student's scientific field, and direct feedback/evaluation to students. At the end of the activity, the presenters as well as the authors distributed a link to check students’ understanding questionnaires about paraphrasing techniques in general. From these activities, it can be concluded that the paraphrasing technique is very important for students and is needed to reduce the percentage of plagiarism check results. In addition, from the results of the questionnaire, overall, all participants understood and could practice well the paraphrase technique material from the Workshop.